Ozone Cleaning of Fouled Poly(Vinylidene) Fluoride/Carbon Nanotube Membranes - Chedly Tizaoui (Ozone: Science & Engineering, 2018)
This research demonstrates for the first time that ozone is an effective cleaning agent for polyvinylidene fluoride (PVDF) membranes fouled by natural organic matter (NOM). Bare PVDF membranes as well as PVDF impregnated with CNTs (pristine (CNTs–P) and oxidized (CNTs–O)) at 0.3% mass membranes were used. Three different methods were investigated for cleaning the fouled membranes including; A: 10-min cleaning by pure water, B: 5-min water followed by 5-min ozonated water, and C: 10-min fully ozonated water. It was found that the application of fully ozonated water for 10 min was very effective to reinstate the flux to almost its original value of unfouled membrane. The CNTs–P/PVDF membrane exhibited the highest fouling with a total fouling ratio of 81%, while for the bare PVDF and the CNTs–O/PVDF membranes, the fouling ratios were 76% and 74%, respectively. The full ozonated water cleaning method gave the highest removal of fouling leaving the lowest irreversible fouling on the membrane as compared to the other cleaning methods. On the other hand, the highest removal of NOM fouling was obtained for CNTs–O/PVDF membranes indicating that fouling on CNTs–O/PVDF membrane was less bound than the other membranes. Contact angle measurements of the fouled membranes showed that all membranes exhibited increased contact angles due to the NOM deposition but after cleaning, particularly with ozonated water, the membrane contact angles returned to almost their original values. FTIR analysis of the membranes corroborated the results obtained.